(3CQHYhf MOjKG aj GdCNdGbs - (3GdYGedj, YR GdOjf, GdMSjf Hf YHO GdUeO Hf eMeO GdLHYj, J (B984(3g` (B1576(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg Ydi fYeGFg GdZRGQ (B... (3hHYO (B... (3deG QhjJ HSfOj GdBJj Yf eMeO Hf jYbhH Gdcdjfj Yf GdMSjf Hf eMeO GdCTYQj (B... (3ef Qhi ef CMGOjKfG CQHYjf MOjKG HYKg Gddg jhe GdbjGeI YGekdG abjgGs
(3BNQgG (B:s
(3BNQgG(B: (3hbGd Ydjg GdSdGe(B: (3EPG CJJ Ydi GdQLd CQHYhf SfI bjd dg NP MPQc aEfc ZjQ eYPhQ hdjS GHf GdCQHYjf HCMb HGdMPQ ef GHf YTQjf aEf GdPj jWdHgeG hGMO hdjS HQGbO aGYed deG CeGec ef Gdghd hOY Yfc aVhd Gdbhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 240s
(3GdPQjYI, L (B1: 255s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs